Functional Outcomes After Total Knee Replacement in Kupang: A Retrospective Cohort Study - Rante, Su Dji To; Kareri, Dyah Rambu; Manafe, Derri RT (Universitas Airlangga, 2025)
Background: Total knee replacement (TKR) is effective for advanced knee osteoarthritis, but its access can be limited by implant and perioperative costs. Our tertiary center in Kupang, Indonesia, adopted a single implant system to support service delivery. This study quantified early functional change using the Oxford Knee Score (OKS) three months after TKR.Methods: We conducted a retrospective single-centre cohort at Siloam Hospital in Kupang, from December 2022 to May 2024. Consecutive adults with Kellgren–Lawrence grade IV knee osteoarthritis who underwent primary TKR with one implant system (Fixamet) were included. The OKS (0–48; higher scores indicate better function) was collected preoperatively and at three months in Bahasa Indonesia using a standardized protocol. Pre–post change was analyzed as paired data.Results: Forty-seven patients were analyzed (mean age 65.77 ± 7.44 years; 80.9% women). The mean OKS improved from 12.53 ± 3.69 preoperatively to 41.02 ± 2.17 at three months, a mean change of 28.48 points (95% CI 27.24–29.70; p < 0.001). One early complication was documented (arthrofibrosis, 2.1%).Conclusions: In this single-centre cohort, TKR was associated with large early improvements in patient-reported knee function at three months. These findings describe early recovery within our service and do not establish comparative effectiveness versus other implant systems. Future studies should follow patients for a longer period, directly compare Fixamet with other implant systems, and include cost-effectiveness analyses to assess both clinical and economic value.